Transient model-based operation guidance on blast furnace. (January 2019) - Hashimoto, Yoshinari; Kitamura, Yohei; Ohashi, Tomohiro; Sawa, Yoshitaka; Kano, Manabu
Abstract: To reduce the heat variance and realize the stable operation of a blast furnace, an operation guidance system was developed. This system involves nonlinear model predictive control based on a new transient model and provides appropriate guidance to operators. Accurate future prediction is a key to success because the huge heat capacity of the blast furnace leads to slow, complex dynamics with long dead time. The online validation results in the actual furnace showed that the standard deviation of the hot metal temperature was reduced by 3.7 °C when the operators followed the guidance provided by the developed system. Highlights: A new transient model for the prediction of hot metal temperature was developed. Hot metal temperature of 8 hours ahead was predicted successfully with the model. Model predictive control based on the developed transient model was established. Variance of the hot metal temperature was reduced by the predictive control.